Analisis Strategi Pemasaran Digital, Kinerja dan Keberlanjutan Usaha Sambal Bara Musi Di Kota Palembang - Valentcia Valentcia; Agrippina Cindy Calista; Yulizar Kasih (MDP Student Conference, 2026)
This study aims to analyze the digital marketing strategy and sustainability of a ready-to-eat chili sauce business in Palembang. Sambal Bara Musi is a business engaged in ready-to-eat packaged products. This business offers five menu variants that are innovative combinations of chili sauce and side dishes. The analysis areas in this study focused on digital marketing strategy analysis, business performance analysis (financial reports), and business sustainability analysis. Based on the analysis results obtained, it can be stated that the Sambal Bara Musi business can be implemented well and sustainably.